Communication Patterns of Adolescent Autism in Expressing Feelings to The Opposite Sex (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Problems in this research is the pattern of communication conducted by adolescent autism in expressing feelings to the opposite sex and the uncontrolled behavior of adolescent autism in expressing the feeling to the opposite sex. The purpose of this study was to describe and explain the communication patterns of adolescent autism in expressing the feeling to the opposite sex as well to explain the uncontrollable behavior that may arise from autistic adolescents when feeling an attraction with the opposite sex. The type of this research is descriptive qualitative with the case study. Subjects in this study were autistic adolescents with an age range of 12 to 22 years, autistic adolescent parents, and teachers/therapists from autistic adolescents. Data collection techniques used are interviews, observation, and documentation. Data analysis techniques by collecting data, organizing data systematically then interpreting data to others. Of the 2 subjects studied showed that communication adolescent autism to the opposite sex that makes them interested tend to passive, 2 subjects cannot communicate their feelings to the opposite sex firmly and clearly. They are more likely to show interest by staring at the opposite sex for long periods of time, walking back and forth near the opposite sex, or following the opposite sex everywhere. Not all autistic teenagers who are getting interested in the opponent have uncontrollable behavior, from 2 subjects there is only 1 who likes to suddenly kiss and hug the opposite sex that attracts him.